Peningkatan Kepuasan Konsumen Internal untuk Material Shipment di PT. X - Stephanie Tanojo; Tanti Octavia (Jurnal Titra, 2014)
PT. X measures internal customer satisfaction using an index called Internal Supplier Service Rate (ISSR) monthly. One of the order intake in PT. X is material that called as material shipment. Currently, Order intake for material shipment was increasing, but the increasing not in line with the ISSR. PT. X only achieved ISSR as 89,5% in 2013 which target is 95%. This final assignment attempts to increase ISSR in material shipment activity. The proposed improvements are standar work flow, material forecast for Supplier, coordination between company and Supplier, and an additional staff for material shipment. The proposed improvements are implemented and the ISSR increases to 97,5%.